Correlation of X-ray diffraction signatures of breast tissue and their histopathological classification. Issue 1 (December 2017) - Moss, Robert; Amin, Amany; Crews, Chiaki; Purdie, Colin; Jordan, Lee; Iacoviello, Francesco; Evans, Andrew; Speller, Robert; Vinnicombe, Sarah
Abstract This pilot study examines the correlation of X-ray diffraction (XRD) measurements with the histopathological analysis of breast tissue. Eight breast cancer samples were investigated. Each sample contained a mixture of normal and cancerous tissues. In total, 522 separate XRD measurements were made at different locations across the samples (8 in total). The resulting XRD spectra were subjected to principal component analysis (PCA) in order to determine if there were any distinguishing features that could be used to identify different tissue components. 99.0% of the variation between the spectra were described by the first two principal components (PC). Comparing the location of points in PC space with the classification determined by histopathology indicated correlation between the shape/magnitude of the XRD spectra and the tissue type. These results are encouraging and suggest that XRD could be used for the intraoperative or postoperative classification of bulk tissue samples.